Metode Pembina Pesantren Tebuireng dalam Meningkatkan Kepercayaan Diri Santri Ditengah Masyarakat: Penelitian - Bagas Setiawan; Khoirotul Idawati (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Islamic boarding schools (pesantren) serve not only as centers for religious and academic development but also play a crucial role in shaping students' character, particularly their self-confidence. This study aims to explore the mentoring methods implemented at Pesantren Tebuireng to enhance students’ self-confidence, enabling them to adapt and actively contribute within society. The research employs a descriptive qualitative approach, utilizing observation, in-depth interviews, and documentation for data collection. Findings reveal that mentors at Pesantren Tebuireng use methods such as role modeling, personal approach, organizational involvement, and training in public speaking and leadership. These approaches effectively foster students’ confidence, independence, and readiness to engage in social life. A supportive and collaborative environment within the pesantren also strengthens the mentoring process. This study recommends consistent and innovative mentoring practices to nurture students who are not only spiritually grounded but also confident and competent in societal settings.